Exploring The Use of Narrative Texts in Teaching Writing for EFL Classroom - Cardianti Qatrinada; Tri Wintolo Apoko (Edulitics (Education, Literature, and Linguistics) Journal, 2024)
Narrative text is one of the writing types used by English teachers to provide to teach, and the use of narrative text is believed to be important for English teachers to apply in EFL English writing classroom. Thus, this study aims to explore the use of narrative texts in teaching English writing at secondary schools and investigate teachers' perceptions of its efficacy in enhancing students' writing skills. This qualitative research investigates the implementation of narrative texts in teaching writing in English as a Foreign Language (EFL) classrooms and explores teachers' perceptions of their use in improving students' writing skills. This research utilizes a qualitative descriptive research design to investigate the implementation of teaching writing through narrative texts and teachers' perceptions of their efficacy in improving students' writing skills. Data collection involved observations and semi-structured interviews with two experienced 10th-grade English teachers in one of reputable private senior high schools in Jakarta, Indonesia. This research highlights the paramount significance of incorporating narrative texts to enhance English writing proficiency among high school students. Despite teachers acknowledging their merits, challenges such as vocabulary constraints and translation hurdles persist. Nevertheless, narrative texts, particularly fairy tales, serve as catalysts for fostering students' creativity and critical analysis. Employing strategies that prompt critical inquiry is imperative. Consequently, narrative texts emerge as indispensable tools in high school English writing pedagogy, demanding innovative methodologies to surmount obstacles and elevate students' writing acumen effectively.